Аssessment of the prospects for growing forest crops of European larch in the Eastern Forest-Steppe of Ukraine - Svitlana Raspopina; Maksim Didenko (Наукові праці Лісівничої академії наук України)
Larix decidua Mill. is of interest in meeting the needs of industry in obtaining fast timber not only in European countries, but it also has significant prospects for cultivation in different natural zones of Ukraine. The main objective of this paper was to study the soil conditions and the state of forest crops of European larch and assess the prospects for its use in the plantation system of cultivation (the cultivation stands with a short rotation age (41-60 years)) in the Eastern Forest-Steppe of Ukraine. For this purpose, a comparative ecological approach was used. In particular, the condition and productivity of forest crops of the introduced species - European larch - were compared with crops of Pinus sylvestrys L. as an aboriginal species, which is also one of the main species that forms forests in Ukraine.